Using Management and Lease-Affermage Contracts for Water Supply : How Effective Are They in Improving Service Delivery - Ringskog, Klas; Hammond, Mary Ellen; Locussol, Alain (World Bank, Washington, DC, 2012)
As governments in developing countries seek to expand access to water supply and improve the quality of service, they are considering a range of options for public-private partnerships. Yet proposals to involve the private sector have often met with concerns - about tariff hikes, staff cutbacks, and ability to reduce inefficiency and expand access to service among the poor. And experience with the more than 300 contracts bringing private operators into water supply in 1990-2004 has been mixed. How have water utilities performed under management and lease-affermage contracts? Eight case studies across developing regions show that performance has generally improved-across a range of measures.